Assessing the temperature of plasma produced in carbon dioxide (CO2) Laser-Induced Breakdown Spectroscopy (LIBS) from soil sample prepared by two different methods of metal mesh and silicone grease. (June 2020) - Sari, A M; Lahna, K; Idris, N; Ramli, M; Kurihara, K; Marwan
Abstract: Temperature of plasma generated by CO2 laser from soil sample prepared by the two different methods, namely metal mesh, and silicone grease methods, was examined. The plasma was produced by focusing the laser beam on the sample at 1 atmospheric pressure. The plasma characteristics namely temperature was estimated by the Boltzmann plot method. The detection was made in region of 300 nm-400 nm. In the case sample prepared using the metal mesh method, the estimated temperature was about 11605 K for the metal mesh no. 50 and 12440 K for mesh no. 40, respectively when helium was used as surrounding gas. When air was used as surrounding gas, plasma temperature was about 10315 K and 10990 K, respectively. In case the soil sample prepared by soil mixed with silicon grease (SMS) smeared on a surface of metal sub target, plasma temperature was about 8913 K and 9218 K for air and helium as a surrounding gas, respectively. It can be concluded that plasma temperature is not significantly different although the sample was prepared with different methods.